AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI EKSTRAK KULIT JERUK MANIS (Citrus sinensis) DAN APLIKASINYA SEBAGAI PENGAWET PANGAN - Ardhia Deasy Rosita Dewi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Microbial contamination may cause food poisoning and a decrease in food quality. Preservatives such as Citrus senensis sweet orange peel waste can be used to extend the shelf life of food. The purpose of this study was to measure the potential antioxidant and antibacterial activity of orange peel extract and its application to improve the quality of meatballs, wet noodles, and tofu. Meatballs, wet noodles, and tofu were soaked with the extract for 90 minutes prior to storage at room temperature (28±2°C) for 4 days. The results showed that the inhibition zone of the extract using disc diffusion assay was 17.67±0.58 mm against Escherichia coli, 16±1 mm against Staphylococcus aureus, and 12.67±1.15 mm against Salmonella Typhi. Sweet orange peel extract had an antioxidant activity of 66.41% with total phenol of 2,656.48±55.46 mg GAE/100g. The extract was able to reduce total bacteria between 0.5 and 1.0 log CFU/g in meatballs, wet noodles and tofu. The application of the extract on meatballs, wet noodles and tofu preserved aroma and color attribute until 4th day of storage at room temperature (28±2°C). Decrease of texture attributes were observed starting from 3rd day of storage at room temperature (28±2°C).